PERBEDAAN PERSEPSI TERHADAP ATRIBUT HOTEL ANTARA WISATAWAN BISNIS DAN NON BISNIS - Luki Adiati Pratomo; Evi Vileta Lanasier (Universitas Trisakti, 2002)
Indonesian tourism industry is one of the important factors in Indonesian economy, it has gone through turbulence condition due to the condition of global economy as well as Indonesian political condition. Hotel as one of the major player in the tourism industry is expected to give their best services for the traveller in order to get tourist back. Different perception on hotel attribute. This research is focused on the difference of traveller perception among business travellers and non business traveller.